Political aspects of economic integration in the Commonwealth Caribbean - Miller, Christina (Tulane University. Graduate School TulaneUS, 1972)
Describes environment for Caribbean integration and discusses integration theory. Examines history of West Indian Federation and the reasons for its failure. Discusses establishment of CARIFTA, its problems and prospects. Reviews attitudes of business and agricultural sectors, labour, and UWI economists to Caribbean integration.